2021
DOI: 10.2147/dddt.s288219
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide Melectin Shows Both Antimicrobial and Antitumor Activity via Membrane Interference and DNA Binding

Abstract: Increasingly complex diseases require novel drugs for their treatment. Antimicrobial peptides (AMPs) are promising candidate treatments due to their broad existence and special characteristics. However, the current understanding of AMPs is not sufficient to allow them to be produced commercially for clinical use. Materials and Methods: Melectin, from the venom of the cleptoparasitic bee Melecta albifrons, does not exhibit sequence homology with other wasp venom peptides. To investigate this more deeply, we exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Melectin, an antimicrobial peptide from the venom of the cleptoparasitic bee Melecta albifrons , does not exhibit sequence homology with other wasp venom peptides. Melectin manifests antitumour activity, penetrates membranes and binds DNA [ 38 ]. The venom of a parasitoid wasp, Pteromalus puparum, contains a peptide with endonuclease activity (PpENVP), which inhibits gene expression in transfected cells relying on two activation sites [ 71 ].…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Melectin, an antimicrobial peptide from the venom of the cleptoparasitic bee Melecta albifrons , does not exhibit sequence homology with other wasp venom peptides. Melectin manifests antitumour activity, penetrates membranes and binds DNA [ 38 ]. The venom of a parasitoid wasp, Pteromalus puparum, contains a peptide with endonuclease activity (PpENVP), which inhibits gene expression in transfected cells relying on two activation sites [ 71 ].…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Besides, melectin reduced the release of TNF-α, IL-1β, IL-6, and IL-8 from S. aureus -stimulated human fibroblasts. These findings suggested that melectin could be considered as a new template against multidrug resistance ( Ko et al, 2020 ; Liang et al, 2021 ).…”
Section: Anti-infectivity Effectmentioning
confidence: 97%
“…In addition to inhibiting cell viability, MEL had high permeability to the plasma membrane of cells in human acute T cell leukemia Jurkat cells, which enhanced the permeability of MEL through the plasma membrane and further caused cell death ( Gasanoff et al, 2021 ). The anti-infectivity peptide melectin from Melecta albifrons , by virtue of its α-helical structure, inhibited cell proliferation by interfering with the cell membrane of leukemic cells K562, decreasing the viability of various cells such as K562, K562/ADM and HL-60 while enhancing LDH output ( Liang et al, 2021 ).…”
Section: Anticancer Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melectin shows low hemolytic activity [ 211 ], and, in mammalian cancer cells, this peptide mainly targets the cell membrane, and, after penetrating the cell, it is able to compromise the whole cell’s integrity [ 199 ]. Asides from that, melectin is also able to bind to plasmid DNA [ 213 ].…”
Section: Antimicrobial Peptides From Insects and Arachnidsmentioning
confidence: 99%